Pod storage with roasting: A tool to diversifying the flavor profiles of dark chocolates produced from 'bulk' cocoa beans? (Part II: Quality and sensory profiling of chocolates). (June 2020) - Hinneh, Michael; Abotsi, Enoch Enorkplim; Van de Walle, Davy; Tzompa-Sosa, Daylan Amelia; De Winne, Ann; Simonis, Julien; Messens, Kathy; Van Durme, Jim; Afoakwa, Emmanuel Ohene; De Cooman, Luc; Dewettinck, Koen
Graphical abstract: Highlights: Comparable quality attributes are necessary for a more objective comparison of chocolate flavor. Both instrumental and sensorial analysis are necessary for a holistic description of chocolate flavor profiles. PS with RT plays a key role in steering the final flavor of chocolate regardless of the bean origin or genetic variety. Odor-active aroma volatiles can be adequate for predicting the sensory perceptions of chocolates to a greater extent. Abstract: The impact of pod storage (PS) and roasting temperature (RT) on the quality parameters and the sensory profiles of dark chocolates were evaluated. Dark chocolates (70%) from ten liquors of different PS and RT combinations as well as six liquors of different origins (Ecuador, Ghana, Ivory Coast, Madagascar, Venezuela and Vietnam) with variable genetic groups were produced under identical conditions and compared. To a greater extent, the range of chocolate quality attributes underscored the generally minimal effects of PS, RT and origin of liquor on the processing conditions. Although with a few exceptions, generally, chocolate acidity (pH and TA) decreased with increasing PS and vice versa in the case of RT. Furthermore, results from a balanced incomplete block design (BIBD) involving a 16-member expert panel also revealed the impact of the applied treatments (PS and RT) on the final flavor profiles of the chocolates irrespective of the origin or genetic groups of the cocoa beans. The same was confirmed when instrumental aroma results were correlated with the sensory data using partial least squares (PLS) regression models. Thus, this study demonstrates the possibility of creating diverse flavor profiles (even towards 'fine' flavor) from 'bulk' cocoa beans through an optimized combination of PS and RT. The findings are therefore expected to challenge the status-quo, especially in the way 'bulk' cocoa is currently processed and consequently priced, thereby, possibly fostering a win-win situation between cocoa producers and industries.